2011
DOI: 10.1159/000323775
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Debulking Surgery Followed by Paclitaxel/Platinum Chemotherapy Is Very Effective in Treating Ovarian Carcinosarcomas: A Single Center Experience

Abstract: Background: There have been only a few reports on the survival and management of patients with ovarian carcinosarcomas. We evaluated the clinical characteristics, outcomes and prognostic factors of ovarian carcinosarcomas. Methods: Retrospective analysis of data obtained from medical records of 40 patients treated at the Asan Medical Center, Seoul, Korea, between January 1989 and January 2008. Results: Median survival was significantly longer in patients <60 years of age than in those ≧60 (p = 0.001), patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…Our findings corroborate other reports that have demonstrated that ovarian carcinosarcoma is an extremely aggressive subtype of epithelial ovarian cancer that is often advanced at diagnosis [24, 10], and that age and stage are associated with overall survival [2, 5, 9, 11, 12]. Furthermore, we showed that extent of primary cytoreductive surgery and residual disease status correlate with outcome, consistent with previous reports.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings corroborate other reports that have demonstrated that ovarian carcinosarcoma is an extremely aggressive subtype of epithelial ovarian cancer that is often advanced at diagnosis [24, 10], and that age and stage are associated with overall survival [2, 5, 9, 11, 12]. Furthermore, we showed that extent of primary cytoreductive surgery and residual disease status correlate with outcome, consistent with previous reports.…”
Section: Discussionsupporting
confidence: 92%
“…Most published data are limited to retrospective reviews, and because of the rarity of the disease, few institutions are able to accrue a sufficient number of patients for prospective studies. Some studies suggest that an optimal surgical cytoreductive effort at the time of primary surgery and adjuvant chemotherapy may be associated with improved overall survival [2, 79]. Our assumptions regarding the best surgical treatments and adjuvant therapies for this disease are extrapolated from studies of patients with epithelial ovarian carcinoma or uterine carcinosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…219 Optimal surgical debulking is recommended for patients with MMMTs (see "Principles of Surgery" in the complete version of these guidelines [OV-A]). 219,[222][223][224] After complete surgical staging, several postoperative chemotherapy regimens are recommended for patients with stage I to IV MMMT. Patients with stage I to IV MMMT may be treated as per epithelial ovarian cancer (see OV-3; page 1138).…”
Section: Carcinosarcomas (Mmmts)mentioning
confidence: 99%
“…According to an analysis of the Surveillance, Epidemiology and End Results data, the rate of OCS is 0.19 per 100,000 women [3]. Despite the rarity of OCS, it is associated with a high rate of cancer-related mortality even at early stages [4]. OCS typically occurs in postmenopausal women at a median age of 65 years and is staged according to FIGO criteria for epithelial ovarian cancer (EOC) [5].…”
Section: Introductionmentioning
confidence: 99%
“…OCS typically occurs in postmenopausal women at a median age of 65 years and is staged according to FIGO criteria for epithelial ovarian cancer (EOC) [5]. More than 70% of patients present with advanced stage (stage III-IV) disease at the time of diagnosis [4]. The most common symptoms resemble those observed with EOC, including pelvic and/or abdominal pain, early satiety, bloating, and abdominal distention [6].…”
Section: Introductionmentioning
confidence: 99%